Pengaturan Umum Mengenai Investasi Serta Keuangan Elektronik Dalam Hukum Teknologi dan Informasi - Ramadhan, Niko Rafael; Alvito, Haykal Rizki; Matondang, Togar Ibrahim; Nugroho, Andriyanto Adhi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Digital investment can also be interpreted as investment activities carried out to gain profits through an online or digital platform. Electronic finance (Electronic Finance) is a form of financial transaction that uses information and communication technology to carry out financial transactions, such as payments, sending funds, etc. History of the ITE Law In Article 1 number 1 of Law no. 14 of 2008 concerning Public Information Openness, 'information' is information, statements, ideas and signs that contain values, meanings and messages, whether words, facts or explanations that can be seen, heard and read which are presented in various forms. packaging and format in accordance with developments in electronic and non-electronic technology and communication. Forms of electronic investment consist of E-Gold, Mutual Funds, and shares as well as electronic finance usually found in E-Wallets. The Electronic Financial Investment Law Justice Institute (Electronic Financial Investment Dispute Settlement Agency) is a regulatory body in Indonesia which is responsible for handling disputes related to electronic financial investments, such as online trading, e-commerce and other digital financial transactions. The Electronic Financial Investment Supervisory Agency is contained in Law Number 21 of 2011 OJK (Financial Services Authority).